Employees job satisfaction at Maybank Kota Kinabalu / Md Suhaimi Othman - Othman, Md Suhaimi (2016)
Job satisfaction is a general thing to be discuss. Due to that, the researcher has decide to explore more what is all about related to term of "job satisfaction". Therefore, the researcher has a plan to study job satisfaction limited to the Maybank Kota Kinabalu Branch at Jalan Pantai. One the purpose of this research is to study what are the problems across related to the job satisfaction among the employees at Maybank Kota Kinabalu. Besides that, this study has indicate level of job satisfaction and factors that contributing to it. The process of conducting questionnaire will cover to all employees inclusive of Management Team and Non-Management team. The technique that will use when distributing questionnaire is non probability sampling. Part of the primary data is questionnaire and it will be divided into 3 section: section A (profile of respondent), section B (independent variable) and section C (independent variable). Besides, the researcher has a plan to find sources from secondary part such as books, magazine, journal, internet, and so on. A l l the information will be analyse through application of SPSS. From the early observation by research, it will be a quiet of numbers difficulty when dealing with private company especially when collecting information. Thus, proper planning and systematic will be use when conducting this research.